Paeoniflorin-free subfraction of Paeonia lactiflora Pall. shows the potential of anti-hepatic fibrosis: an integrated analysis of network pharmacology and experimental validation. (5th December 2022) - Zhang, Qian; Wu, Yuzhuo; Ge, Maoxu; Xia, Guiyang; Xia, Huan; Wang, Lingyan; Wei, Xiaohong; He, Hongwei; Lin, Sheng
Abstract: Ethnopharmacological relevance: Hepatic fibrosis is a major consequence of liver disease. Radix Paeoniae Rubra (RPR), the dry root of Paeonia lactiflora Pall., has a long history of clinical application in traditional Chinese medicine (TCM) for the treatment of liver diseases. The researches of RPR active ingredients are mainly focused on paeoniflorin. However, the functional roles of other ingredients have not been clarified sufficiently in the treatment of hepatic fibrosis with RPR. Aim of the study: This study was to figure out the anti-hepatic fibrosis potential and mechanisms of CS-4, one of the paeoniflorin-free subfraction of RPR. Materials and methods: With the guide of bioassay, CS-4, a subfraction of RPR showed in vitro inhibition of hepatic stellate cell activation, was obtained using multiple chromatographic techniques. Its ingredients were determined by UPLC-Q-TOF-MS/MS. Then, the target profiles of ingredients were obtained from the HERB database, and the disease targets were collected from the DisGeNET database. Through the network pharmacology method, a protein-protein interaction network of CS-4 against hepatic fibrosis was established to analyze and excavate the potential therapeutic targets. Combined with the KEGG analysis, a series of signaling pathways were obtained, thereby validated by western blot analysis. Results: The paeoniflorin-free subfraction of RPR, CS-4, was obtained and showed the most potential anti-fibrotic effect in vitro . A total of 20 main ingredients were identified from CS-4 and considered as its active ingredients. From HERB and DisGeNET databases, 1460 potential targets of CS-4 and 1180 disease targets were obtained, respectively. The overlapped 79 targets were considered to exert the potential anti-fibrosis effect of CS-4, such as JAK2, MYC, SMAD3, and IFNG. The gene enrichment analysis revealed that classical TGF-β/Smad signaling pathway and nonclassical TGF-β/PI3K-AKT signaling pathway may be two of the main mechanisms of CS-4 against hepatic fibrosis, which supported by western blot analysis. Conclusion: In this study, a paeoniflorin-free subfraction with potential anti-hepatic fibrosis activity in vitro, CS-4, was obtained from RPR. Its multiple ingredients, multiple targets, and multiple mechanisms against hepatic fibrosis were explained by network pharmacology and verified by western blot analysis to further support the clinical applications of RPR. Graphical abstract: Image 1 Highlights: A paeoniflorin-free subfraction of Paeonia lactiflora Pall. was first reported. Its main ingredients were identified by UPLC-TOF-MS/MS. Its complex mechanisms of anti-hepatic fibrosis were clarified by network pharmacology. Parts of signaling pathways were verified by experiments.